Belize : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper describes economic developments in Belize during the 1990s. Following a strong performance in the late 1980s, Belize's economy weakened in 1991-93, mainly because of a substantial deterioration in the fiscal position. The overall deficit of the nonfinancial public sector increased from 1\2 percent of GDP in FY1990/91 to about 7 1\2 percent in FY1992/93 owing to a substantial increase in the government wage bill and in domestically financed capital outlays. The net domestic assets of the financial system increased by about 20 percent a year during 1991-93.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet